Thucydides' war narrative : a structural study - Dewald, Carolyn (Berkeley, Calif. : University of California Press, 2005)
A sustained analysis of the connections between narrative structure & meaning in the 'History of the Peloponnesian War' this volume focuses on the evident change in the underlying principles of the history at the conclusion of the first ten years.
CONTENTS; List of Tables; Preface; Introduction; 1. An Overview of the Archidamian Narrative Structure (ii. 1-v.24); 2. Introductory Sentences (ii. 1-v.24); 3. Internal Structure of the Unit of Action (ii. 1-v.24); 4. Patterns Formed by Units of Action in the Archidamian Narrative (ii. 1-v.24); 5. The Years of the Peace (v.25-vi. 7): The Unit of Action Changing; 6. Years Seventeen through Twenty-one (v.8-viii. 109): The Unit of Action Transformed; 7. Some Conclusions: Thucydides' Narrative Structures (ii. 1-viii. 109); Notes; Bibliography; General Index; Index Locorum.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Thucydides; Thucydide; History of the Peloponnesian War (Thucydides); Greece -- History -- Peloponnesian War, 431-404 B.C. -- Historiography; Grèce -- Histoire -- 431-404 av. J.-C. (Guerre du Péloponnèse) -- Historiographie; HISTORY -- Ancient; HISTORY -- Ancient -- General; Historiography; Greece; Historiae (Thucydides); Vertelkunst; Greece; Regions & Countries - Europe; History & Archaeology; 431-404 B.C; History